Oxidation stability of lubricating base oils. (1st February 2018) - El-Naggar, A.Y.; El-Adly, R. A.; Altalhi, T. A.; Alhadhrami, A.; Modather, F.; Ebiad, M. A.; Salem, A.
ABSTRACT: The oxidative stability of three base lubricating oils of different grades light, medium and heavy oils (B1, B2 and B3, respectively) was studied at oxidative times 50, 100 and 150 hours. The quality of base oils under investigation were evaluated on the basis of total acid number, vaporization loss, kinematic viscosity and quantity of sludge formed. Also, the chemical composition of the studied lubricating oils was achieved via capillary gas chromatography. The comparative study of the oxidative performance of the base oils showed that the higher degrees of heavy oil than light one. The increase in the oxidation time led to increases of the evaporation loss and lubricant viscosity. Analysis of a lubricant's oxidation stability therefore contributes to a better understanding of its effectiveness under normal operating conditions and its suitability for formulating automotive lubricants. The aim of this work is the study the Potential life of lubricant oils inside engine motor at different oxidative times in view of their oxidation stability.